Adequate Nutrition May Get You Home: Effect of Caloric/Protein Deficits on the Discharge Destination of Critically Ill Surgical Patients. (January 2016) - Yeh, D. Dante; Fuentes, Eva; Quraishi, Sadeq A.; Cropano, Catrina; Kaafarani, Haytham; Lee, Jarone; King, David R.; DeMoya, Marc; Fagenholz, Peter; Butler, Kathryn; Chang, Yuchiao; Velmahos, George
Background : Macronutrient deficit in the surgical intensive care unit (ICU) is associated with worse in-hospital outcomes. We hypothesized that increased caloric and protein deficit is also associated with a lower likelihood of discharge to home vs transfer to a rehabilitation or skilled nursing facility. Materials and Methods : Adult surgical ICU patients receiving >72 hours of enteral nutrition (EN) between March 2012 and May 2014 were included. Patients with absolute contraindications to EN, <72-hour ICU stay, moribund state, EN prior to surgical ICU admission, or previous ICU admission within the same hospital stay were excluded. Subjects were dichotomized by cumulative caloric (<6000 vs ≥6000 kcal) and protein deficit (<300 vs ≥300 g). Baseline characteristics and outcomes were compared using Wilcoxon rank and χ 2 tests. To test the association of macronutrient deficit with discharge destination (home vs other), we performed a logistic regression analysis, controlling for plausible confounders. Results : In total, 213 individuals were included. Nineteen percent in the low-caloric deficit group were discharged home compared with 6% in the high-caloric deficit group ( P = .02). Age, body mass index (BMI), Acute Physiology and Chronic Health Evaluation II (APACHE II), and initiation of EN were not significantly different between groups. On logistic regression, adjusting for BMI and APACHE II score, the high-caloric and protein-deficit groups were less likely to be discharged home (odds ratio [OR], 0.28; 95% confidence interval [CI], 0.08–0.96; P = .04 and OR, 0.29; 95% CI, 0.0–0.89, P = .03, respectively). Conclusions : In surgical ICU patients, inadequate macronutrient delivery is associated with lower rates of discharge to home. Improved nutrition delivery may lead to better clinical outcomes after critical illness.